Azoxystrobin Induces Apoptosis of Human Esophageal Squamous Cell Carcinoma KYSE-150 Cells through Triggering of the Mitochondrial Pathway - Shi, Xiao-ke; Bian, Xiao-bo; Huang, Tao; Wen, Bo; Zhao, Ling; Mu, Huai-xue; Fatima, Sarwat; Fan, Bao-min; Bian, Zhao-xiang; Huang, Lin-fang; Lin, Cheng-yuan (Frontiers in Pharmacology, 2017)
Recent studies indicate that mitochondrial pathways of apoptosis are potential chemotherapeutic target for the treatment of esophageal cancer. Azoxystrobin (AZOX), a methoxyacrylate derived from the naturally-occurring strobilurins, is a known fungicide acting as a Qo inhibitor of mitochondrial respiratory complex III. In this study, the effects of AZOX on human esophageal squamous cell carcinoma KYSE-150 cells were examined and the underlying mechanisms were investigated. AZOX exhibited inhibitory effects on the proliferation of KYSE-150 cells with IC50 of 2.42μg/ml by 48h treatment. Flow cytometry assessment revealed that the inhibitory effect of AZOX on KYSE-150 cell proliferation occurred with cell cycle arrest at S phase and increased cell apoptosis in time-dependent and dose-dependent manners. Cleaved poly ADP ribose polymerase (PARP), caspase-3 and caspase-9 were increased significantly by AZOX. It is worth noted that the Bcl2/Bax ratios were decreased because of the down-regulated Bcl2 and up-regulated Bax expression level. Meanwhile, the cytochrome c release was increased by AZOX in KYSE-150 cells. AZOX-induced cytochrome c expression and caspase-3 activation was significantly blocked by Bax Channel Blocker. Intragastric administration of AZOX effectively decreased the tumor size generated by subcutaneous inoculation of KYSE-150 cells in nude mice. Consistently, decreased Bcl2 expression, increased cytochrome c and PARP level, and activated caspase-3 and caspase-9 were observed in the tumor samples. These results indicate that AZOX can effectively induce esophageal cancer cell apoptosis through the mitochondrial pathways of apoptosis, suggesting AZOX or its derivatives may be developed as potential chemotherapeutic agents for the treatment of esophageal cancer.